ANALISIS PENGARUH MANAJEMEN MODAL KERJA DAN LEVERAGE TERHADAP GROSS PROFIT MARGIN - Jusmansyah, Muhamad (Universitas Budi Luhur, 2020)
This study aims to analyze the Effect of Working Capital Management and Leverage on Gross Profit Margin in the 2013 - 2017 Building Construction Sub Sector Companies listed on the Indonesia Stock Exchange.The data used is secondary data and the analysis method used is multiple linear regression analysis with the help of Statistical Product and Service Solution (SPSS) version 20.0 to obtain a comprehensive picture of the relationship between one variable and another. The sample in this study consisted of eight (8) companies in the construction construction sub-sector listed on the Indonesia Stock Exchange (IDX) in observations from 2013 to 2017 with a purposive sampling method as a sampling method. The results of this study are Number of Days Account Receivable and Debt to Total Assets have an effect on Gross Profit Margin. Number of Days Inventory, Number of Days Account Payable and Cash Conversion Cycle have no effect on Gross Profit Margin.